Tumor vaccines - Frank Bertoncelj, Mojca (Radiology and oncology (Ljubljana), 2006)
Tumor vaccines have several potential advantages over standard anticancer regirrcents. They represent highly specific anticancer therapy. Inducing tumor-specific memory T-lymphocytes, they have potential for long-lived antitumor effects. However, clinical trials, in which cancer patients were vaccinated with tccmor aaccines, have been so far mainly disappointing. There are many reasons for the inefficiency of tumor vaccines. Most cancer antigens are normal self-molecules to which imrrtune tolerance exists. That is why the population of tumor-specific lymphocytes is represented by a small number of low-affinity T-lymphocytes that induce weak antitumor immune response. Simultaneously, tumors evolve many mechanisms to actively evade immune system,what makes them poorly immunogenic or even tolerogenic. Novel irrtmunotherapeutic strategies are directed toward breaking immune tolerance to tumor antigens, enhancing immunogenicity of tumor vaccines and overcoming mechanisms of tumor escape. There are several approaches, unfortunately, all of them still far away from an ideal tumor vaccine that would reject a tumor. Difficulties in the activation of antitumor immune response by tumor vaccines have led to the development of alternative immunotherapeutic strategies that directly focus on effector mechanisms of immune system (adoptive tumor-specific T-lymphocyte transfer and tumor specific monoclonal antibodies).
Keywords: Adjuvants, Immunologic; Antibodies, Monoclonal; Antigeni novotvorb; Antigens, Neoplasm; Cancer Vaccines; cepiva; Drug Therapy; Imunostimulatorji; imunoterapija; Neoplasms; Novotvorbe; Novotvorbe, cepiva; Protitelesa monoklonska; therapy; tumor; zdravljenje